Internal Factors Of Business And Internal Individual Affecting Entrepreneurial Activity And Business Growth Of Broiler Chickens In Province - Rufti Puji Astuti (JASc (Journal of Agribusiness Sciences), 2018)
The purpose of the study in general is to determine the factors that affect the growth of broiler business in the eastern zone of Jambi Province. These factors are focused on internal factors, namely the internal factors of individuals and internal factors of business. The objectives of the research are 1) to identify the internal factors of the individual that influence the growth of the business 2) to identify the internal factors of the individual business affecting the growth of the business and 3) to analyze the influence of internal factors of internal factors and internal factors on business growth. The research was conducted by survey method. Analysis and Data Processing using Stuctural Equation Modeling (SEM) and Smart Patial Least Square (Smart-PLS 2.0). The results showed that innovation, risk taking, and production power are internal factors of individual and internal business that affect business growth. Both factors are known to be significant and positively affect business growth. This study also found that business growth is influenced by internal factors of individual and internal business indirectly, that is through a series of entrepreneurial activities undertaken by farmers. Both have a positive relationship, meaning that the diversity of the growth of broiler farming business in Jambi Province occurs because of the encouragement of entrepreneurship activities of farmers, driven by internal factors of individuals and internal factors of business.